2022
DOI: 10.1186/s12885-022-09762-3
|View full text |Cite
|
Sign up to set email alerts
|

CKAP2L, a crucial target of miR-326, promotes prostate cancer progression

Abstract: Background The overexpression of aberrant cell cycle signaling pathway associated protein has been implicated in multiple malignancies and the identification of all-important one among is the crux of the precise targeted therapy. CKAP2L (Cytoskeleton Associated Protein 2 Like) plays a newish role in cancer progression through activation of the process of cell cycle and mitosis. In this study, we aim to delineate the prominent dysregulated expression of CKAP2L and comprehensively reveal its dere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Flow cytometry results showed that knockdown of CKAP2L resulted in cell cycle G2/M arrest. Similar to previous studies 5 7 , we suggested that CKAP2L may contribute to tumor progression in KIRC by influencing the biological behavior of cancer cells through the cell cycle too. However, we only validated the effect of CKAP2L in KIRC and further studies are needed to assess the role of CKAP2L in the other tumors.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Flow cytometry results showed that knockdown of CKAP2L resulted in cell cycle G2/M arrest. Similar to previous studies 5 7 , we suggested that CKAP2L may contribute to tumor progression in KIRC by influencing the biological behavior of cancer cells through the cell cycle too. However, we only validated the effect of CKAP2L in KIRC and further studies are needed to assess the role of CKAP2L in the other tumors.…”
Section: Discussionsupporting
confidence: 90%
“…CKAP2L is a mitotic spindle protein that has been previously shown to be overexpressed in some tumors and to be associated with tumor progression and patient prognosis. In prostate cancer, esophageal squamous cell carcinoma and glioblastoma, CKAP2L has been shown to affect the biological behavior of cancer cells by regulating the cell cycle 5 7 . A breast cancer study has shown that CKAP2L activates the AKT/mTOR signaling pathway and thus promotes breast cancer development 9 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation